Peran Guru dan Orang Tua dalam Edukasi Keuangan Sejak Usia Dini: Menanamkan Nilai Menabung, Berbagi, dan Konsumsi Bijak di Yayasan Pendidikan Islam Tajaul Karomatu, Desa Situ Gadung, Tangerang - Ahmad Nur Ihsan; Ahyani Ahyani; Ainurohmah Ainurohmah; Amirudin Amirudin; Elsa Khanaya Putri; Ruth Vera Evelyna (Jurnal PKM Manajemen Bisnis, 2026)
Financial education from an early age is essential for shaping responsible financial behavior and instilling positive values related to money management. This community service program (PKM) was carried out to strengthen the role of teachers and parents in introducing the values of saving, sharing, and wise consumption among young children. The activity took place at Yayasan Pendidikan Islam Tajaul Karomatu, Desa Situ Gadung, Tangerang, on August 31, 2025. The program was implemented by six lecturers from Universitas Pamulang and involved 35 participants consisting of teachers and students. The methods used included material presentations, practical exercises, discussions, and question-and-answer sessions. During the activity, participants were provided with interactive learning materials and demonstrations designed to encourage children to practice saving habits, generosity, and prudent spending behavior in their daily lives. The results of the PKM showed an increase in participants’ understanding of early childhood financial education concepts and greater awareness of the collaborative roles of teachers and parents in guiding children’s financial literacy. Participants also expressed enthusiasm for applying the knowledge gained in classroom and home environments. Overall, this program successfully fostered engagement, knowledge sharing, and sustainable practices in early financial education within the school community.